Передумови смарт-спеціалізації Донецько-Придніпровського макрорегіону на основі розвитку хімічного виробництва - Amosha, Oleksandr I.; Shevtsova, Hanna Z.; Shvets, Natalya V. (Institute of Industrial Economics of NAS of Ukraine, 2019)
The article highlights the problems of forming regional strategies and determining development priorities in the context of implementation of the smart specialization concept in old industrial regions. The growing scientific interest in this concept is driven by the importance of engaging the best modern European practices to the modernization of regional development policy in Ukraine. The additional applied significance of the work is related to the need for regional and sectoral refinement of common approaches and substantiation of smart priorities within the ongoing process of regional strategic planning.The controversial issues of the traditional specialization of regions and the use of the potential of existing industry clusters are considered. The necessity and possibility of transforming the development path of old industrial regions and their clusters using the smart specialization approach are emphasized.The current state, institutional structure, dynamics, factors and challenges of the chemical sectors development of Dnipropetrovsk, Donetsk, Zaporizhia and Luhansk regions are analyzed. It is concluded that it is advisable to involve available resources and competences in the chemical and related sectors of these regions to generate new areas of specialization and regional growth points based on diversification, neoindustrial modernization and organization of sectoral and cross-sectoral synergies. Such opportunities are due to the systemic impact of modern chemical production on the innovative development of other sectors of the economy and its significant role in high-tech value chains.Practical ideas on the areas of smart specialization of particular regions of Donetsk- Pridneprovsky macro-region are given. These proposals are based on historically formed features of the territories, local concentration of resources, available chemical manufacturing potential, configuration and experience of the informal clusters and characteristics of regional innovative ecosystems. Special attention іs paid to the chemical production development in Donetsk and Luhansk regions in light of the challenges of post-conflict reconstruction and modernization of the Donbass economy.